PENGARUH ETIKA PROFESI TERHADAP PENCAPAIAN STANDAR KUALITAS GURU DI ERA TEKNOLOGI INFORMASI - Sarwiti, Sarwiti; Sari, Rosita Kusuma; Sumarni, Ani; Nurlaely, Eli; Kholifah, Siti (LPPM Universitas Bina Bangsa, 2025)
The rapid advancement of technology in the digital era has significantly transformed the field of education, including the roles and responsibilities of teachers. Amid these changes, maintaining the quality of education through enhancing teacher professionalism becomes crucial. One key aspect of improving teacher professionalism is the application of professional ethics, which plays a strategic role in addressing the challenges of the digital age. This paper aims to analyze how professional ethics contribute to enhancing teacher quality by emphasizing the importance of values such as honesty, accountability, and transparency in utilizing educational technology. This study employs a qualitative approach with document analysis techniques to review various relevant literature on professional ethics and its application in modern education. The findings indicate that implementing professional ethics is essential for fostering public trust in the teaching profession, improving the quality of digital interactions between teachers and students, and minimizing the misuse of technology in classrooms. Thus, strengthening the application of professional ethics in teaching not only positively impacts student learning outcomes but also reinforces the role of teachers as moral exemplars in society.